Design of Electrocardiograph Signal Simulator - Catur Suharinto; Anwar Budianto; Nugroho Tri Sanyoto (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2020)
Medical equipment functional test and calibration is a routine activity that must be carried on periodically. Electrocardiograph (ECG) requires an ECG phantom to calibrate the function. This calibrator is commonly called ECG signal simulator. The purpose of this study is to design a simple ECG signal simulator with ten leads of signals that can be used to test ECG recorders with standard recording procedures. With the ECG signal simulator that was designed and made, the development of signal patterns can be made as needed. The normal human cardiac signal displayed on the ECGSIM software. The potential value that displayed on ECGSIM software can be extracted manually and assembled as a flash program of microcontroller, so this microcontroller will generate some digital code by each parallel port. This digital code then converted as an analog signal by DAC. The electrocardiograph signal simulator output is an analog signal that identical with each lead according to the recording method of bipolar, unipolar and precordial of ECG. This analog signal was tested using a standard ECG recorder. It is proved that the simulator is able to generate an electrical signal in accordance with the characteristics of the human cardiac signal displayed on ECGSIM software. The results of human electrocardiograph signal simulator design are a device that generates electrical signals with output specifications that correspond to the bioelectric signals of the human heart. The statistical test showed that the p-value is more than 0.05. It is mean that there is no significant difference between the design and standard. The signals pattern has met the specification of ECGSIM signal